Prevalence of depression in the smoking population from a municipality in the State of Sergipe, Brazil - Cardoso, Tarcísio Nascimento; Azevedo, Antônio Carvalho; Dantas, Cley Gabriel Lima Carvalho; Santos, Marcos Daniel Seabra; Oliveira, Makson Gleydson Brito de; Melo, Mônica Santos de (Research, Society and Development, 2024)
Smoking is one of the leading preventable causes of death and is associated with the development of serious diseases, such as cancer and cardiovascular issues. In 2019, more than 8 million people died from diseases linked to tobacco use. Globally, about 22.3% of the adult population uses tobacco, while in Brazil, it is estimated that 25.6% of adults are smokers. The relationship between smoking and mental health is complex and reciprocal, with studies showing that tobacco can both contribute to and result from mental disorders, especially depression. Smokers with mental health disorders tend to consume more tobacco, worsening its impact on their mental health. The objective of this article is to present the results of a survey on the prevalence of depression in the smoking population. An exploratory, field research, was carried out, with a quantitative approach, collecting data from 96 smoking patients in the Municipality of Lagarto, State of Sergipe. The data indicated a significant correlation between the intensity of tobacco use and the severity of depressive symptoms. However, the duration of use did not show a significant impact on depression, suggesting the influence of other factors. These findings reinforce the need for public policies focused not only on reducing smoking but also on supporting smokers’ mental health, with integrated interventions that include medical and psychological approaches.